(untitled) (World Bulletin of Management and Law, 2025)
In the modern economy, digital transformation is acquiring the status of a key factor determining the competitiveness of small and medium-sized businesses (SMEs). This article analyzes the theoretical aspects of digital transformation, the tools for implementing digital technologies, as well as their correlation with the dynamics of economic growth. Particular attention is paid to identifying the benefits of the digitalization process, as well as identifying barriers and risks relevant to SMEs.